1972
DOI: 10.1021/ed049p772
|View full text |Cite
|
Sign up to set email alerts
|

Freshman chemistry without lectures. A modified self-paced approach

Abstract: Describes the use of the Keller systems and its results in a freshman chemistry course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Close to the end of each Wednesday evening lecture, a four item (occasionally three) multiple 1 Ronald Martin. 2 Classes were scheduled by the registrar on the basis of a student's total time table, the result being that the students were unable to select which class they would enter which helped ensure random groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close to the end of each Wednesday evening lecture, a four item (occasionally three) multiple 1 Ronald Martin. 2 Classes were scheduled by the registrar on the basis of a student's total time table, the result being that the students were unable to select which class they would enter which helped ensure random groups.…”
Section: Methodsmentioning
confidence: 99%
“…While small student groups seem ideally suited for this method, some efforts have also been made to use it on larger ones. In chemistry teaching the method was put to use on a group of 81 at the University of Texas at Austin (2), and perhaps there are several other larger groups which we are unaware of. In the fall of 1972, at the University of Western Ontario, we had little experience with the Keller method; hence we were reluctant to try it here on groups of 150 to 200 students taking freshman chemistry.…”
mentioning
confidence: 99%
“…It differs from the Keller plan in the question of pacing: students must, complete five of the 16 units by the end of the sixth week (of ten) of instruction. Such instructor-pacing (5)(6)(7) was added to the course early in its development when it was observed that students at complete liberty to set their rate of progress failed in disturbing numbers to set any pace at all. Students not meeting the deadline are dropped from the course.…”
mentioning
confidence: 99%
“…Although required to complete courses within one semester, students have for the most part found themselves in the novel situation of self-pacing, i.e,, having been able to determine their own rate of unit completion for the whole semester (4, 6, 7, 9-13, 16, 17, 19-21, 24, 25). Even though the use of deadlines has been reported (2,26), only one deadline was used in each case, occurring approximately three to four weeks into each course. Requiring tests to be taken on specified dates only appears to have been tried in one study (8).…”
mentioning
confidence: 99%
“…Although examinations common to both PSI and lecture-discussion groups represent a more reliable basis, comparisons baaed on exams (4,9,16,18,23,24) and course grades have suffered from both the uncertain equivalence of the groups being compared due to the need to work with intact rather than randomly selected groups, and the differential loss of students. This threat to validity has been even greater where performance comparisons have been made between different student populations across different semesters on the basis of both examination scores (5,8,12,16,22) and course grades (2, 3, 6,8,26). Pasternack (19) addressed this problem by selecting PSI and lecture-discussion groups at random; however, interpretation of the results is complicated by the fact that not all students wrote the same exam, and scores were adjusted to account for differences in difficulty of the exams.…”
mentioning
confidence: 99%